2019
DOI: 10.1111/pde.14011
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 gain‐of‐function and chronic demodicosis

Abstract: Heterozygous STAT1 gain-of-function (GOF) mutations result in a combined form of immunodeficiency which is the most common genetic cause of chronic mucocutaneous candidiasis (CMC). We present a pedigree with a GOF mutation in STAT1, manifesting with chronic demodicosis in the form of a facial papulopustular eruption, blepharitis, and chalazion. So far, demodicosis has been described in only one family with STAT1-GOF mutation. We suggest that chronic demodicosis is an under-recognized feature of the immune dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Ruxolitinib, a JAK family tyrosine kinase inhibitor has been a successful therapy in a patient with severe CMC 9 ; its therapeutic response could be explored in STAT1-GOF inflammatory manifestations. The presence of rosacea in the family described in this study, along with the patients reported with early-onset rosacea from two unrelated kindreds, 4,5 and at least the cutaneous phenotype depicted as 'figure 2 D.P104' (erythema, telangiectasias and papulopustules) reported by Toubiana et al, 7 (we may suggest having a rosaceiform dermatosis) supports that STAT1-GOF is a monogenic aetiology of rosacea. Therefore, the presence of early-onset rosacea may be considered as suspected for a STAT1-GOF defect in patients who may display autoimmune, infectious and/or autoinflammatory manifestations.…”
Section: Rosacea As a Striking Feature In Family Members With A Stat1supporting
confidence: 86%
See 3 more Smart Citations
“…Ruxolitinib, a JAK family tyrosine kinase inhibitor has been a successful therapy in a patient with severe CMC 9 ; its therapeutic response could be explored in STAT1-GOF inflammatory manifestations. The presence of rosacea in the family described in this study, along with the patients reported with early-onset rosacea from two unrelated kindreds, 4,5 and at least the cutaneous phenotype depicted as 'figure 2 D.P104' (erythema, telangiectasias and papulopustules) reported by Toubiana et al, 7 (we may suggest having a rosaceiform dermatosis) supports that STAT1-GOF is a monogenic aetiology of rosacea. Therefore, the presence of early-onset rosacea may be considered as suspected for a STAT1-GOF defect in patients who may display autoimmune, infectious and/or autoinflammatory manifestations.…”
Section: Rosacea As a Striking Feature In Family Members With A Stat1supporting
confidence: 86%
“…3 To date, a genetic cause for early-onset rosacea has only been described in two unrelated families, with a gain-of-function (GOF) mutation in STAT1. 4,5 Here, we report eight family members affected with STAT1-GOF; six of them with rosacea with four of the latter showed early onset.…”
Section: Rosacea As a Striking Feature In Family Members With A Stat1mentioning
confidence: 90%
See 2 more Smart Citations
“…[8][9][10][11][12] The Demodex density (Dd) thus increases with age. 3,[13][14][15][16][17] Many factors have been reported to favor proliferation of the Demodex mite, including immunosuppression, [18][19][20][21][22][23] hypervascularizationrelated factors 10,[24][25][26][27][28] (likely via vascular endothelial growth factor [VEGF], 12 which has immunosuppressive properties 29 ), lack of use of soap combined with cosmetic overuse, 30 male sex, 13,31 high concentration of sebaceous glands 7,16 (such as on the cheeks 4,14,32,33 ), sebaceous hyperplasia, 3,6 and poor blood glucose control. 21 Other factors (e.g., low skin moisture, 14,33 low sebum quantity, 33,34 altered sebum composition, 33,35 and skin alkalinity 35 ) may be more a consequence of Demodex proliferation than a cause, because Demodex proliferation probably disturbs sebaceous gland function in the same way it induces Meibomian gland dysfunction on the eyelas...…”
Section: Introductionmentioning
confidence: 99%